Does poverty predict religion? - Hoverd, William J. (Religion, brain & behavior, 2013)
The question of how religion relates to poverty has long fascinated social scientists, yet answers remain elusive. Deprivation theory holds that lower socio-economic standing is associated with higher religious identification, but not with religious affiliation. Cross-cultural support, however, is limited. The present study addressed this gap by testing the predictions of deprivation theory using a large (n =6,518) national probability sample of New Zealanders. A key innovation of our study is the use of an objective index of neighborhood deprivation derived from a Principle Components Analysis of New Zealand Census data. Consistent with deprivation theory, we found that neighborhood deprivation predicted religious identification, but not religious affiliation. Adding education to the model improved fit, but did not attenuate the effect of deprivation. Importantly, the addition of ethnicity to the deprivation model produced a better fit for predicting the strength of religious identification. These results suggest a role for cultural inheritance in explaining the mechanisms by which religious identity and religious affiliation are related to each other, and over time. Finally, we consider these findings through a discussion that integrates evolutionary models of religion with the sociological model of deprivation theory.